A Demand Strategy Framework For The Ophthalmology Market In The Philippines: A Model For The Pharmaceutical Industry - Castro, Gerardo Merano; Esmeraldo M, Dimaculangan (International Journal of Business Economics (IJBE), 2024)
Purpose – This study aims to analyze the factors that influence the prescribing habits of Filipino ophthalmologists.Methodology – A total of 20 Filipino ophthalmologists were interviewed to identify the attributes they look for in an ophthalmic drug. The gathered attributes were then subjected to conjoint analysis, resulting in 31 attribute combinations. To determine the importance of these attributes, a conjoint survey was conducted with 318 respondents who ranked the attributes based on their significance. Pearson correlation coefficient and Kendall t-tests were performed to evaluate the model's fit and determine whether the attributes affect physicians' prescribing habits. Additionally, path-worth analysis was conducted to assess the importance of attribute scores and level values.Findings – The results showed that Filipino ophthalmologists prioritize quality, free drug samples, and the patient's economic status. Conversely, price was found to be the least important attribute. Furthermore, the path-worth of variables indicated a higher preference for high efficacy/tolerability, one unit of sample per visit, and no sponsorship of continuing medical education (CME) but participation in conventions. Ophthalmologists also favored generics, purite/polyquad preservative, and a price range of ₱801 and up. Partial detailing of pharmaceutical representatives with 4 times or more per month visit and personal relationships were also prioritized. However, patients' economic status was not a significant consideration in their prescribing decisions. Originality/Novelty – This study is unique because it delves into the various factors that affect the prescribing practices of Filipino ophthalmologists, analyzing each attribute in detail. This is a novel approach that hasn't been thoroughly explored in previous research, and it could be the first of its kind both in the Philippines and abroad. Implications – This research study can be helpful for the healthcare industry to identify the key product attributes and their corresponding levels that affect the prescribing habits of physicians. By doing so, firms can develop targeted marketing strategies and better patient-centered programs for healthcare providers. Furthermore, this study can encourage future research on similar subject matters and incorporate key learnings in classroom discussions related to business courses.